Flexible Subjects: Educational Policy Neoliberal Rationalities - Gomez Sanchez, Lucia; Navas Saurin, Almudena; Bernad Garcia, Joan Carles (Education Policy Analysis Archives, 2005)
Flexible Subjects: Neo-liberal Rationalities and Education Policy. This article aims to examine training and employment programmes for the young (more specifically, the Spanish Social Guarantee Schemes—Programas de Garantía Social) in relation to neoliberal political rationalities. We believe the introduction of neoliberal policies to have been greater and faster precisely in the periphery of the educational system. To that end, we intend to make teachers' participation in the operation of the policies conceptually visible. The professionals’ discourse about the socio-labour integration of the young –a discourse that legitimises their daily work – will be analysed on the basis of qualitative materials from in-depth interviews. This analysis allows us to: 1) show the new ways of defining and valuing the teaching activity required and generated by these practical and institutional changes; 2) the analysis evidences some of the effects of the emerging discourses as well as the strategic roles they play in connection with neoliberal governance styles.